Limitation of minimum price of immovable property in the enforcement procedure in the law of Republic of Serbia and in the law of Republic of Croatia - Radovanović, Miloš S (Pravni zapisi, 2014)
The provision of Article 97 paragraph 6 of the Law on Enforcement and Security, Official Gazette of RS no. 31/11, 99/11, 109/13, provides that the immovable property of the enforcement debtor, after two failed public auctions, may be sold without limiting the minimum price. The Croatian Law contained a provision with the same substance. The Constitutional Court of the Republic of Croatia, acting on constitutional petitions, proclaimed that rigid application of the Croatian provision had violated debtor’s right on fair trail.Author will compare standpoint of the Constitutional Court of the Republic of Croatia with standpoints of the highest Serbian judicial instances regarding mentioned provision of Serbian law. This stand of domestic courts, as well as the stand of the Croatian Constitutional Court is based on the prohibition of disposals of parties that are contrary to enforceable statutes and rules of decency.The legal solution, which provides that immovable property in the enforcement proceedings be sold without limitation of minimum prices in Croatia has been abandoned. The stands of the highest courts of the Republic of Serbia, as well as the Croatian example show the manner in which mentioned provision of Serbian law should be interpreted, but also the direction in which it should be changed.